2D GeSe/SnS2(SnSe2) broken-gap heterostructures for tunnel field-effect transistors applications. (21st August 2019) - Wang, Tianxing; Zhang, Qian; Li, Jingbo; Xia, Congxin
Abstract: Two-dimensional (2D) materials-based van der Waals heterostructures (vdWHs) provide a platform to realize novel physical phenomena for future nanoelectronic devices. Here, our theoretical results indicate that the 2D GeSe/SnS2 (SnSe2 ) vdWHs possess the broken-gap band alignment and can be potentially utilized in the tunnel field-effect transistors (TFETs). Moreover, negative electric field can keep type-III band alignment and enlarge the tunneling window, while the positive electric field can transform the type-III to type-I or type-II band alignments for the GeSe/ SnS2 (SnSe2 ) vdWHs. Thus, these studies open the way to fabricate the 2D materials-based TFETs and the possibility of multi-functional nanodevices applications.